Influence of National Culture on Perspectives and Factors Affecting Student Dropout: A Comparative Study of Australia, Saudi Arabia, and Ethiopia - Singh, Harman Preet; Alhamad, Ibrahim Abdullah (Archives of Business Research, 2022)
Student dropout is a complex issue with significant repercussions for educational institutions and nations. Using the Hofstede national culture model, this study assessed the various social, psychological, economic, and organizational factors that influence student dropout. Since developed, developing, and least-developed countries score differently on the Hofstede model, Australia, Saudi Arabia, and Ethiopia were selected as representative nations. The evaluation indicates that social factors may have a low, moderate, and high influence on student dropout rates in Australia, Saudi Arabia, and Ethiopia, respectively. Different organizational factors may influence student dropout rates in Australia, Saudi Arabia, and Ethiopia. In Australia and Ethiopia, psychological factors may play a larger role in student dropout than in Saudi Arabia. In Australia and Ethiopia, economic factors may play a larger role in determining student attrition than in Saudi Arabia. In Australia, the dropout rate among female students may not be a major concern, while it could be a more prominent concern in Ethiopia and Saudi Arabia. However, in Saudi Arabia, such concerns are mitigated by the substantial financial assistance provided by the government to students pursuing an education.